Virtual Laboratory Science to Improve Students' Science Literacy Ability - Dina Rahmi Darman; Imaningtyas Imaningtyas; Nina Nurhasanah; Linda Zakiah; Nursifa Fauziah; Dewi Rahayu Ningsih; Firmanul Catur Wibowo; Andi Suhandi; Ida Kaniawati; Achmad Samsudin; Beken Arymbekov (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2026)
Technological developments in education demand innovation in learning media to overcome the limitations of laboratory facilities and conventional methods, especially in elementary science education. Prospective elementary school teachers need to have strong scientific literacy to support meaningful learning. This study aims to develop a Virtual Science Laboratory (VSL) as a flexible, interactive, technology-based medium to improve students' Scientific Literacy Skills (SLA). The approach used is Research and Development (R&D) with the model Analysis, Design, Development, Implementation, Evaluation (ADDIE). Data were collected from 120 prospective elementary school teachers in Jakarta, Indonesia, aged 21–23 years. SSC was measured through a science literacy test (pretest-posttest) and analyzed with Normalized gain (N-Gain). The results showed that VSL significantly improved scientific literacy, with an average increase of 59.4% (moderate effect size). Each aspect of SLA increased: Explanation of Scientific Phenomena (61%), Interpretation of Data & Evidence (77%), Evaluation & Experimental Design (42%), Use of Scientific Evidence (58%), and Awareness of Scientific Applications (59%). These findings demonstrate the effectiveness of VSL as an innovative solution for technology-based science learning, particularly in contexts with limited physical lab space. VSL is recommended for integration into science education curricula as a 21st-century learning approach to support the professional competency of prospective teachers. Keywords: virtual laboratory, science education, science literacy, student ability, learning innovation.